Beras Analog Talas: Mengkaji Potensi Pasar di Tengah Trend Pangan Alternatif - Ashlihah, Ashlihah; Widyaningsih, Bekti; Zuhria, Siti Aminatuz (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2024)
ABSTRACTIndonesia, which has a large population, relies on rice as the main staple food. In recent years, there has been a growing trend of food alternatives as a government strategy in local food diversification. Taro analog rice has emerged as a food innovation to replace rice. Taro analog rice is one of the solutions to expand food choices and support dietary diversity. This product has high nutritional value and can be produced more efficiently under certain conditions. This article aims to assess the market potential of taro analog rice in Indonesia, by looking at the opportunities and challenges that exist amidst the growing trend of alternative food. This research employs a qualitative methodology with descriptive techniques to examine the market prospects for taro analog rice in Indonesia, framed against the backdrop of alternative food trends. Data pertinent to this investigation was collected through a systematic review of the literature.  Analog rice is a food product designed to resemble conventional rice, both in terms of form and nutritional composition. In this case, taro was chosen as the main raw material as it has good nutritional characteristics, including a lower glycemic index compared to white rice. The Promising Role of Taro as a Substitute for Traditional Rice in the Domestic Market and in the international scale market, the demand for analog rice is increasing. However, the challenge remains in market education and distribution. Collaboration between producers, government, and research institutions is needed to develop efficient processing technologies and strengthen distribution networks. This study concludes that taro analog rice can be a leading product in the Indonesian and international markets, providing benefits to individual health and the local economy. Keywords: Alternative Food Trends, Analog Taro Rice, Market Potential  ABSTRAKNegara Indonesia yang memiliki populasi besar, bergantung pada nasi sebagai makanan pokok utama. Dalam beberapa tahun terakhir ini semakin berkembangnya trend alternatif pangan sebagai strategi pemerintah dalam diversifikasi pangan lokal. Beras analog talas muncul sebagai inovasi pangan pengganti beras. beras analog talas sebagai salah satu solusi untuk memperluas pilihan pangan dan mendukung keberagaman diet Masyarakat. produk ini memiliki nilai gizi yang tinggi dan dapat diproduksi dengan lebih efisien dalam kondisi tertentu. Artikel ini bertujuan untuk mengkaji potensi pasar beras analog talas di Indonesia, dengan melihat peluang dan tantangan yang ada di Tengah trend pangan alternatif yang semakin berkembang. Penelitian ini menggunakan metodologi kualitatif dengan teknik deskriptif untuk memeriksa prospek pasar beras analog talas di Indonesia, dibingkai dengan latar belakang tren makanan alternatif. Data yang berkaitan dengan penelitian ini dikumpulkan melalui tinjauan sistematis literatur. Beras analog adalah produk pangan yang dirancang untuk menyerupai beras konvensional, baik dari segi bentuk dan komposisi gizi. Dalam hal ini, talas dipilih sebagai bahan baku utama karena memiliki karakteristik gizi yang baik, termasuk indeks glikemik yang lebih rendah dibandingkan dengan nasi putih. Peran Talas yang Menjanjikan sebagai Pengganti Beras Tradisional di Pasar Domestik dan dalam pasar skala internasional, permintaan beras analog semakin tinggi. Namun, tantangannya masih ada pada edukasi pasar dan distribusi. Kolaborasi antara produsen, pemerintah, dan lembaga penelitian diperlukan untuk mengembangkan teknologi pengolahan yang efisien dan memperkuat jaringan distribusi. Penelitian ini menyimpulkan bahwa Beras analog talas dapat menjadi produk unggulan di pasar Indonesia dan internasional, memberikan manfaat bagi kesehatan individu dan ekonomi lokal.Kata Kunci: Tren Pangan Alternatif, Beras Analog Talas, Potensi Pasar